Factors Affecting Patient Safety Incident Reporting - Galuh Meifika Fathiyani; Dian Ayubi (Journal Research of Social Science, Economics, and Management, 2022)
Patient safety incident reporting is one of the steps taken needed to improve patient safety. Reporting can provide a broad picture of the incident and how it happened. This can be used as basic data for policy making and making patient safety programs in hospitals. The subjects in this study were health workers. This research method uses a systematic review, from various sources of research that has been done previously. The databases used in this study are Science Direct, Scopus and SpringerLink, journals published from January 2011 to December 2021 which were then extracted using PRISMA 2009 flowcharts. So that the final results were 11 journals that were reviewed. This study resulted in reporting patient safety incidents influenced by individual factors, group/unit factors and organizational factors. The conclusion of this study is that incident reporting can be improved by evaluating and improving individual factors, group/unit factors and organizational factors